2013
DOI: 10.1007/s10067-013-2267-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of clinical features of bone and joint lesions between children and parents with Kashin–Beck disease in Northwest China

Abstract: We investigated the clinical features of bone and joint lesions in children with Kashin-Beck disease (KBD) and the association of these features with their parents to determine specific clinical features for diagnosing KBD. A total of 2,248 children (4 to 18 years old) and their parents were examined by stratified cluster sampling from 33 villages in six endemic counties and from six villages in a non-endemic county. We collected individual information, clinical symptoms, and radiological signs of the right ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…For instance, collagen catabolic process, protein activation cascade, cellular response to growth factor stimulus, skeletal system development, and extrinsic apoptosis were significantly enriched among the KBD-related genes, indicating that biological events such as the maintenance of apoptosis, the degradation of ECM, and biology process related to oxidative stress play key roles in the development of KBD. Studies had reported that KBD is characterized as specific pathological changes in cartilage, causing apoptosis and necrosis of chondrocytes in the epiphyseal plate, [3,3237] which further demonstrated by our results. The current view about what factors lead to articular chondrocyte apoptosis in KBD focuses on varying degrees of oxidative stress occur in the articular chondrocytes, which is primarily caused by articular chondrocyte apoptosis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For instance, collagen catabolic process, protein activation cascade, cellular response to growth factor stimulus, skeletal system development, and extrinsic apoptosis were significantly enriched among the KBD-related genes, indicating that biological events such as the maintenance of apoptosis, the degradation of ECM, and biology process related to oxidative stress play key roles in the development of KBD. Studies had reported that KBD is characterized as specific pathological changes in cartilage, causing apoptosis and necrosis of chondrocytes in the epiphyseal plate, [3,3237] which further demonstrated by our results. The current view about what factors lead to articular chondrocyte apoptosis in KBD focuses on varying degrees of oxidative stress occur in the articular chondrocytes, which is primarily caused by articular chondrocyte apoptosis.…”
Section: Discussionsupporting
confidence: 88%
“…Of these patients, nearly 13 thousand were children under 13 years old. [2,3] KBD patients usually exhibit the clinical symptoms, such as enlargement of phalanges or other joints, joint pain, limited movement, deformed limb joints. [46] Besides the detrimental effect on all aspects of quality of life, KBD places a heavy economic burden on society as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…However, awareness of this disease is important because of the recent overseas migration of the Chinese. The disease involves lesions of the growth plate and articular cartilage and is often observed in both children and their parents [ 16 ], although there is no pathological change around the epiphyseal cartilage and epiphyses plate after the epiphyseal cartilage ceases to develop in adult KBD patients [ 17 ]. Adult KBD patients should be differentially diagnosed from primary osteoarthritis patients through their history, age, or residence during childhood and characteristic deformities [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A typical distinction of KBD from OA or other bone and joint diseases is the damage of epiphyseal cartilage and hyaline cartilage in the deep zones of cartilage 11,14 . This distinction might explain the occurrence of severe joint deformities during development in young people with KBD 15 .…”
mentioning
confidence: 97%